INFLUENCE OF ALKALINE – EARTH METALS ON ANODIC BEHAVIOR OF ALLOY ССУЗ IN NEUTRAL ENVIRONMENT OF THE ELECTROLYTE NaCl - I. N. Ganiev; O. Kh. Niyezov; N. M. Mulloeva; B. B. Eshov (Литьë и металлургия)
The anodic behavior of a lead-antimony alloy (3 wt% Sb) doped with alkaline-earth metals was investigated in potentiostatic method in the potentiodynamic mode at a potential sweep rate of 2 mV/s and it was shown that with an increase in the content of alkaline earth metals in the alloy (SSUZ), the potentials of free Corrosion and pitting are slightly shifted to the positive region. As the concentration of the chloride ion in the electrolyte increases, these potentials decrease. The current density of corrosion and, accordingly, the corrosion rate of alloys with an increase in the content of alkaline earth metals are reduced by 75–85%, and the concentration of chloride ion increases.In transition from alloys with calcium to alloys with strontium, the corrosion rate of alloys increases by 20–30%, and to alloys with barium it decreases by 25–30%.